Dodana vrednost v izdelkih v gozdno-lesni verigi - Kropivšek, Jože (Les (Ljubljana), 2017)
The potential of wood raw material in the Slovenian forest wood supply chain is often insufficiently exploited. The promotion of its more rational use, while having indirect effects on the wider economic environment, is necessary to: (1) ensure the effective functioning of the entire forest wood supply chain, providing products with high added value; and (2) fully exploit the potential of wood raw material in terms of quality. In the article we examined added value of beechwood products, identified key challenges in this evaluation, and the relationships with other economic indicators that affect business decisions. Beechwood products were classified according to the amount of value added, and thereby the potential of beechwood raw materials was demonstrated in terms of both the impact on society and economic development. We thus confirmed the importance of the development and operation of the entire forest wood supply chain, and the importance of government economic policy in its functioning. More specifically, the state of primary wood processing as an important part of forest wood supply chain in Slovenia was examined, and some reasons for its ineffectiveness were identified. The availability of raw materials based on quality and purpose of use, and the value added per cubic meter of beechwood, were assessed in order to prove the reasonableness of investments in the newest technologies for hardwood processing and veneer production
Keywords: added value; assessment of market potential; beechwood; bukovina; dodana vrednost; forest wood supply chain; gozdno-lesna veriga; primarna predelava lesa; primary wood processing